Efforts to Strengthen Nationalist Character Education through Education and Community Empowerment Institutions in the Indonesia-Malaysia Borderlands - ., Imran; Ramadhan, Iwan; ., Daniel; ., Suriyanisa (Journal of Ecohumanism, 2025)
Border communities between countries are the frontline of a country. However, this is sometimes neglected by the government of a country. The position of border communities can be used as an illustration of the face of a country. The different levels of economic, social and cultural life of two neighboring countries sometimes become opportunities and threats between neighboring countries. The urge to fulfill economic, educational and cultural needs is sometimes the reason why people still love their homeland or leave their homeland, or the choice of still living in their homeland but economically, socially and culturally in neighboring countries. This research aims to describe the efforts made by the Government of Indonesia to see how efforts are made to maintain, foster and instill the value of the nationalism character of the border people. The research setting is in the border region of West Kalimantan. The research was conducted using a qualitative approach with a case study design with various information through observation and interviews and documentation. Data analysis using qualitative methods. The results showed that there were at least four (4) activities carried out to instill the character of nationalism to the border community, first by socializing cross-border stakes, border community economic programs, a series of commemorations. Indonesia’s independence day, and socialization through educational channels by conducting socialization to school students at the junior and senior high school levels.